A Comprehensive Database and a New Model for the Axial Response of Heat-Damaged Concrete Before and After FRP Confinement - Demir, Uğur; Akdag, Nefise; Demir, Ugur (Springer, 2025)
In this study, a total of 330 concrete specimens, compiled from existing experimental data, are systematically reviewed to assess their post-fire axial stress-strain behavior before and after circumferential confinement with fiber-reinforced polymers (FRPs). The selection criteria for the database are as follows: (i) studies had to be published in English, (ii) both lateral and axial ultimate strains must have been measured, (iii) the use of additional strengthening materials in combination with FRPs was excluded, (iv) only plain concrete specimens were considered, and (v) specimen dimensions and instrumentation details had to be explicitly reported. The dataset is structured to include heating/cooling and curing conditions, specimen properties, and FRP characteristics. Subsequently, the predictive accuracy of available models for post-fire axial strength and ultimate strain of concrete members, both before and after FRP confinement, is evaluated. The results based on the reviewed comprehensive database indicate that these models are inadequate in capturing the observed behavior in the experiments. As such, a new analytical model is developed based on the compiled dataset. The proposed model demonstrated reliable predictive performance in terms of post-fire axial response of concrete before and after FRP confinement while remaining user-friendly for practical engineering applications. This is done such that universal design guidelines on the behavior of heat-damaged concrete strengthened by FRP composites can be reliably formulated.
Keywords: Concrete; Fire; FRP; Modelling; Repair; Strengthening